(untitled) (Global Journal of Human-Social Science, 2011)
The present paper discusses issues of challenges of social security systems in Sudan Following parameters advanced by ILO and UNCOSOC those systems are analyzed The conclusions focus on their applicability that faces axial difficulties mainly presented in the state of institutional interregnum facing the country Moreover it is important to revisit aspects of social cohesion that serves greater role in traditional social security in the Sudan